Effect of Various Plant Extracts on Dry Root Rot of Chillies Caused by Sclerotium rolfsii - G Bindu Madhavi; S L Bhattiprolu; V Bali Reddy (Journal of Horticultural Sciences, 2011)
Eight different plant extracts were evaluated in vitro against Sclerotium rolfsii causing dry root rot in chillies. Among these, leaf extract of neem (Azadirachta indica) caused maximum inhibition of mycelial growth (80.74%), followed by periwinkle Vinca rosea (78.8%) and bottlebrush (Callistemon, 74.8%) respectively. Sclerotial production was inhibited to an extent of 11% and the inhibition caused was maximum with neem extract, followed by Polyalthia longifolia and V. rosea extracts. Though sclerotial germination was inhibited by 30% to 95% in various treatments, the most effective treatment was that of neem leaf extract (95%), followed by ginger extract (92%).